Sure! Here's a simpler version that a 6th grader might write:
To solve for \( m \) in the equation \( y = mx + b \), just follow these steps:
-
Start with the equation: \[ y = mx + b \]
-
First, get rid of \( b \) by subtracting it from both sides. This helps us focus on \( m \): \[ y - b = mx \]
-
Next, we need to find \( m \). To do that, we will divide both sides by \( x \): \[ \frac{y - b}{x} = m \]
-
So now we can write it like this: \[ m = \frac{y - b}{x} \]
And that's it! The formula for \( m \) is: \[ m = \frac{y - b}{x} \]
It helps to break it down into easy steps!